Stochastic analysis of standby robot-safety systems - Cheng, Shen (University of Ottawa (Canada), 2007)
Nowadays, the application of robots covers almost all aspects of our daily life. They are used to perform increasing complex and critical operations. The increased critical applications have led to various reliability and safety problems, especially many people are injured and killed every year. This study presents reliability and availability analyses of six different standby robot-safety systems: one robot and (n-1) standby safety units with a perfect switch, one robot and (n-1) standby safety units with an imperfect switch, (n-1) standby robots and one safety unit with a perfect switch, (n-1) standby robots and one safety unit with an imperfect switch, n parallel robots and (m-1) standby unit with a perfect switch, and two parallel robots and one standby unit with an imperfect switch. With the aid of Markov and supplementary variable methods, general expressions for system state probabilities, system availability, reliability and mean time to failure were obtained. Plots of some of these expressions are shown to demonstrate the effect of varying failure rates or repair rates of the safety unit, and other parameters.
Keywords: Engineering, Mechanical.; Engineering, Robotics.